Examining dual method contraceptive use among midwestern parenting Latinx teens: Perspectives from adolescent parents, caretakers, and nurses. Issue 5 (12th July 2020) - Ruiz, Yumary; Riciputi, Shaina; Alexander, Stewart C.; DeMaria, Andrea L.; Guilamo‐Ramos, Vincent
Abstract: Background: Despite dual method (DM) contraception being effective in reducing repeat‐births and sexually transmitted infections (STIs), Latinx adolescent parents who live in non‐traditional migration areas remain vulnerable for both outcomes. Objective: This study applied the Unified Theory of Behavior (UTB) and drew upon Bronfenbrenner's social ecological model to explore multiple stakeholders' (adolescent parents, caregivers, and nurses) perceptions of factors that influence DM intentions and use among Latinx adolescent parents. Methods: Semi‐structured interviews with Latinx adolescent parent–caregiver dyads and nurses were analyzed using thematic analysis. Results: Study findings revealed that while all participant groups considered medical providers as DM influencers, contradicting views related to caregivers' as DM influencers emerged among adolescent parents and caregivers. Findings suggest that DM is deemed both acceptable and effective; and adolescent parents' reported DM self‐efficacy. DM obstacles included negative emotions, environmental constraints, and poor knowledge and skills. Conclusions: Study results suggest that constructs from the UTB framework are useful in identifying individual and social factors that can potentially influence DM intentions and use among Latinx adolescent parents. Implications for public health nursing: This study's findings have potential implications for public health nurses interested in designing community‐based interventions to reduce repeat‐births and STIs among Latinx adolescent parents.